Scanning electron microscope assessment of several resharpening techniques on the cutting edges of gracey curettes - Andrade Acevedo, Roberto Antonio; Sampaio, José Eduardo Cezar [UNESP]; Shibli, Jamil A. (My University, 2007)
Aim: Treatment of periodontal diseases is based on efficient scaling and root planing (SRP) and adequate maintenance of the patient. The effectiveness of SRP is influenced by operator skill, access to the subgingival area, root anatomy, and the quality and type of instrument used for SRP. The aim of this study was to evaluate the cutting edges of Gracey curettes after manufacturing and after resharpening using several techniques. Methods and Material: The cutting edges of a total of 41 new #5-6 stainless steel Gracey curettes were evaluated blindly using scanning electron microscopy (SEM). The quality of the cutting edges was evaluated blindly by a calibrated examiner using micrographs. Data were analyzed using a Kruskal Wallis test and nonparametric two-way multiple comparisons. Results and Conclusions: Different sharpening techniques had significantly different effects on the sharpeness of cutting edges (p<0.05). Sharpening by passing the lateral face of curettes over a sharpening stone and then a #299 Arkansas stone produced a high frequency of smooth, sharp edges or slightly irregular edges between the lateral and coronal faces of the curettes. Sharpening by passing a blunt stone over the curette's lateral face produced the poorest quality cutting edge (a bevel). Sharpening of the coronal curette face produced extremely irregular cutting edges and non-functional wire edges. Sharpening with rotary devices produced extremely irregular cutting edges.
Keywords: Curettes; Dental scaling; Periodontal diseases; Root planing; Scaling and root planning; Scanning electron microscopy; comparative study; dental equipment; dental technology; human; instrumentation; methodology; nonparametric test; preventive dentistry; scanning electron microscopy; Dental Instruments; Dental Scaling; Humans; Microscopy, Electron, Scanning; Statistics, Nonparametric; Technology, Dental